Optimalisasi Pelayanan TPS3R di Kelurahan Panjunan Menggunakan Metode Contingent Valuation Method - Muhammad Farsya Indrawan Putra; Iwan Juwana (Jurnal Serambi Engineering, 2024)
Recycling Facility Hikmah was built to provide solid waste management in the Panjunan Sub-district, Astanaanyar District, Bandung City. Recycling Facility Hikmah has the ability to operate continuously, but is still not running optimally due to cost constraints. This research was conducted to identify the potential for improving Recycling Facility management based on residents' willingness to participate in improving waste services through increasing retribution. The Contingent Valuation Method (CVM) is used as a survey technique using direct questionnaires and bidding game techniques, while statistical analysis will be carried out to determine the relationship between the observed variables. Based on the research results, the Willingness to Pay (WTP) value was obtained for 118 people from the 145 respondents interviewed. The Estimated WTP Value (EWTP) is IDR 6,822 and the Total WTP (TWTP) is IDR 4,848,866/month. Based on multiple linear regression analysis, the WTP value for Panjunan Village is influenced bythe type of work and total income